About the Presence of Slamkania pseudosordida (Slamka, 2019) in Turkey (Lepidoptera: Pyralidae, Phycitinae) - K. Akin (SHILAP, 2022)
With this study, the presence of S. pseudosordida (Slamka, 2019) in Turkey is confirmed and it is recorded for the first time in the fauna of Turkey. The record of the species for the Syrian fauna is also discussed. In addition, the pictures of S. pseudosordida and S. sordida (Staudinger, 1879) are present in the study.